Catatan Diversitas Jamur di Salah Satu Pulau Terluar Republik Indonesia: Notes on the Diversity of Macrofungi at one of the Outermost Islands in the Republic of Indonesia - Nurdiyanti, Meilisa Dwi; Suharti, Asrie; Amelya, Mega Putri; Putra, Ivan Permana (Departemen Biologi, Institut Pertanian Bogor, 2020)
Marore Island (Province of North Sulawesi) is one of the outermost island in Indonesia. The island is located at the borderline within the Philippines. Till date, there is no publication about islands macrofungi diversity from this island. In fact, the diversity of macrofungi has the potency to support the development of global bioeconomic in Indonesia. The purpose of this study is to make an inventory list of macrofungi on Marore Island in order to enhance the potential in the future. A total was of 22 mushrooms from 13 genera were obtained from this study which were divided into two phylums, namely Basidiomycota and Ascomycota. The identification results confirmed the species obtained: Ganoderma sp.1, Ganoderma sp.2, Ganoderma sp.3, Ganoderma sp.4, Ganoderma sp.5, Ganoderma sp.6, Trametes sp.1, Trametes sp.2, Trametes sp.3, Pycnoporus sp.1, Pycnoporus sp.2, Polyporus sp., Daedalea sp., Lentinus sp., Marasmius sp.1, Marasmius sp.2, Schizophyllum sp., Panellus sp., Tricholoma sp., Phallus sp., Dacryopinax spathularia, and Daldinia sp.